EFEKTIVITAS PSIKOEDUKASI PAIN MANAGEMENT DALAM MENGURANGI NYERI TUBUH PADA DEWASA LANSIA DI POSYANDU LANSIA X - Agustina Engry (EXPERIENTIA : Jurnal Psikologi Indonesia, 2018)
The purpose of this research is to find out the effectiveness of pain management psychoeducation to decrease pain on elderly people in the integrated healthcare center X. This study used a quasi experimental research with 25 participants that are members of integrated healthcare center X. The type of quasi experimental designs is one group pretest posttest design. Instrument that used is Geriatric Pain Measure from Ferrell, Stein & Beck (2000) that has adapted to bahasa Indonesia. Data analysis used Paired T Test with sig 0,044 that means there is a significant difference pain score before and after pain management psychoeducation has given.